STUDENTS’ ERRORS IN PRONOUNCING THE WORDS CONTAINING SILENT LETTERS AT EFL CLASS - Nurmila,; Yasim, Sukmawati; Khatimah, Nur Husnil (English Language, Linguistics, and Culture International Journal, 2023)
The purposes of this study were to determine the types of errors that Senior High School students make in pronouncing words silent letters and the causes that influence students to make errors in pronouncing words containing silent letters. The approach used in this research was qualitative descriptive. The research subject chosen by using purposive sampling technique were class XI students at SMA Negeri 1 Campalagian in the 2022/2023 academic year. The data were collected by test and interview, then analyzed it by using analytical technique of Miles and Huberman, namely by reducing data, displaying data and drawing conclusion/verification. The results of this study indicated that the types of errors made by students in pronouncing words containing silent letters exist two, Pre-systematic errors and Systematic errors. The results of this study also showed that the causes that influence students in made errors were the lack of experience of students in learning English, pronunciation viewed as one of difficult subject, influenced by the mother tongue and students learning model. From the results of this study, it can be concluded that there are still many students who made errors in pronouncing words that contain silent letters and do not understand how to pronounce the sounds of these words correctly. Keywords: Student Errors, Pronunciation, Silent Letters